Determinants of participation of smallholder farmers in the marketing of small grains and strategies for improving their participation in the Limpopo River basin of Zimbabwe - Minde, Isaac J. (University of Pretoria, 2013)
Dissertation (MScAgric)--University of Pretoria, 2010.